Removal Potential of Basic Dyes and Lead from Water by Brewer's Yeast Biomass. (2nd January 2019) - Lin, Han-Hui; Stephen Inbaraj, B.; Kao, Tsai-Hua
Abstract: The brewing by-product brewer's yeast biomass (BYB) was evaluated as a bioadsorbent for removal of basic dyes and lead from aqueous solutions. The functional groups including the hydroxyl group and cyano group are the major sources of adsorption by BYB. The adsorption of dyes on BYB was negatively correlated with temperature, whereas with lead, it was positively correlated with temperature. The adsorption kinetic of methylene blue (MB), malachite green (MG), and lead on BYB were identified as pseudo-second order, whereas safranin O (SO) was identified as pseudo-first order. A low dosage of BYB effectively adsorbed four adsorbates and reached equilibrium in 3–5 min. The maximum monolayer adsorption capacities of BYB for MB, MG, SO, and lead were 212.05, 212.05, 76.77, and 106.88 mg/g, respectively.